PENINGKATAN HASIL BELAJAR IPADENGAN PENDEKATAN SAINTIFIK PADA SISWAKELAS V SD NEGERI 164522 TEBING TINGGI - Nursia Sitorus (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2019)
The aim of this research is to improve learning result on science subject  through scientific approach. This classroom action researchconducted by 2 cycles of the four phases: planning, implementation, observation, reflection. The subjects of this researchwere students from gradeV, SDN 164522 Tebing Tinggi which amounted to 35 students. This research used a qualitative descriptive analysis technique. Based on data obtained from the measurement of the student learning outcomes on the cycle I was80% and cycle II amounted to 88,57 %. It means that learning the science using scientific approachcan improve learning outcomes in gradeV SDN 164522 Tebing Tinggi. Keywords : Scientific, sciences, qualitative descriptive analysis technique.